Identification, Expression and IAA-Amide Synthetase Activity Analysis of Gretchen Hagen 3 in Papaya Fruit (Carica papaya L.) during Postharvest Process - Liu, Kaidong; Wang, Jinxiang; Li, Haili; Zhong, Jundi; Feng, Shaoxian; Pan, Yaoliang; Yuan, Changchun (Frontiers in Plant Science, 2016)
Auxin plays essential roles in plant development. Gretchen Hagen 3 (GH3) genes belong to a major auxin response gene family and GH3 proteins conjugate a range of acylsubstrates to alter the levels of hormones. Currently, the role of GH3 genes in postharvest physiological regulation of ripening and softening processes in papaya fruit is unclear. In this study, we identified seven CpGH3 genes in a papaya genome database. The CpGH3.1a, CpGH3.1b, CpGH3.5, CpGH3.6, and CpGH3.9 proteins were identified as indole-3-acetic acid (IAA)-specific amido synthetases. We analyzed the changes in IAA-amido synthetase activity using aspartate as a substrate for conjugation and found a large increase (over 5-fold) during the postharvest stages. Ascorbic acid (AsA) application can extend the shelf life of papaya fruit. Our data showed that AsA treatment regulates postharvest fruit maturation processes by promoting endogenous IAA levels. Our findings demonstrate the important role of GH3 genes in the regulation of auxin-associated postharvest physiology in papaya.